Water stress effects on perennial grasses growth and behaviour - Kallida R.; Al Faïz C.; Shaimi N. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In a glasshouse experiment, six cultivars of perennial grasses were tested under imposed water stress. The aim of the trial was to analyse some drought effects on grasses behaviour and water use efficiency. Some physiological indicators associated with drought were used (such as osmotic regulation and sugar accumulation). Differences in varieties response under water constraints were highlighted. Dry matter production was higher for festuca cultivars, followed by phalaris and then cocksfoot. Correlation between dry matter production and water consumption was highly significant. Moderate water stress gave the best results. Festuca cultivars were the most water efficient. The phalaris Atlas and cocksfoot Kasbah had the lowest WUE. In contrast, Lutine fescue had the highest WUE followed by Fraydo, Medly and Sirolan, which gave comparable values. The two cocksfoot, Medly and Kasbah, and the phalaris Sirolan seemed to maintain their leaf relative water content while experiencing drought conditions, assuming some traits of drought tolerance. The varieties Atlas, Sirolan and Medly made better adjustments by maintaining their osmotic potentials almost unchanged over the drought period and then by decreasing their osmotic potential more quickly afterwards.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)